PROSELYTIZING DEVELOPMENT IN SABAH: A HISTORICAL STUDY ABOUT 1946-1990 - Mahmad, Muhamad Amar (Universitas Islam Negeri Alauddin Makassar, 2015)
This article issues about the spread and development of Islam in Sabah around 1946-1990. The period was terrible as the society of Sabah mostly went with the belief of animism, paganism, and the practices of khurafat (related to the myth). During the period, the proselytizers considerably faced challenges of Christian action which was massively spread by British colony. In addition to this, the method of this study is the library research along with a number of opinions among graduates towards discussing this issue. Consequently, it is found that the primary role of spreading and development of Islam during the period was much set the group of Sufisms, the merchants, and the moving foreigners from Sabah such Malay Brunei and the Buginese of Indonesia. Furthermore, the existence of Islam over the world and the appearance of Dakwah organization in this country is the result of scarification who did not feel tired at all. In order to continuously survive the values of Islam around Sabah, the proselytizers, after the period, necessarily have short-term and long-term planning.